Rancang bantun industri kecil suku cadang / komponen kulit teknis untuk industri tekstil - Suliestiyah Wiryodiningrat; Dwi Asdono Basuki (Majalah Kulit, Karet, dan Plastik, 1995)
The objective of this research is to find out proses of production and relation between cost, Selling price anda break even point (BEP). Product specification is space parts for Textile industries i.e.Picker, Buffer, Bumper leather, Sweel leather, Box front leather, Stick Bumper and Tension brake leather. The production capacity is 700 units per-day, so that in one year is 210.000 units. The economical analysis showed that Total Captal (fixed capital and working capital) =Rp. 149.189.750.00. Total production cost per-year (fixed cost and variable cost) Rp. 364.939.375.00. The manufacturing cost = Rp. 12.165 for 7 spareparts. Profit calculation before taxing = Rp. 57.310.625.00 and after taxing Rp. 45.848.500.00. Percentage of the pay out periode calculation of profit to return the capital (rate of return). Before taxing is 38.40%, after 30.73%. equal with 2 years 6 months (before taxing) and after taxing is 3 years. The break even point calculation = Rp. 207.347.274,00 (49,10%) and the capacity is 14.732 units.    INTISARI Penelitian ini bertujuan untuk mengetahui proses produksi dan hubungan antara biaya, harga jual serta perhitungan rugi-laba. Spesifikasi produk suku cadang industry tekstil, yaitu : Picker, Buffer, Bumper leather, Swell leather, Box front leather, Stick Bumper dan Tension brake leather. Kapasitas produksi 700 buah/hari, sehingga per-tahun = 210.000 buah. Analisa ekonomi menunjukkan bahwa Total Modal (modal tetap dan modal dan modal kerja) = Rp. 149.89.750,00 biaya produksi 1 tahun (biaya tetap dan biaya tidak tetap) = Rp. 364.939.375,00. Harga pokok Rp, 12.165,00 (untuk 7 jenis komponen); ke untungan sebelum pajak Rp. 57.310.625,00 dan setelah dipotong pajak Rp. 45.848.500,00